Understanding Student Needs through Student Needs Analysis: Case Study at SMA Negeri 1 Wanadadi - Ridlwan, Faishal; Rahmawati, Heny Kristiana (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Understanding Student Needs through Student Needs Analysis: Case Study at SMA Negeri 1 Wanadadi. Needs Analysis of Students (NAS) is an approach used in guidance and counseling to identify the specific needs of students in various aspects of development. This study aims to understand the needs of students at SMA N 1 Wanadadi to design more effective guidance and counseling interventions. This research employs a quantitative descriptive method with a survey approach. Data were collected through an NAS questionnaire adapted from the counseling questionnaire model, involving twelfth-grade students as respondents selected using purposive sampling. The questionnaire consists of four main domains: personal, social, academic, and career. The research findings indicate that the personal domain is the most dominant aspect, with a need percentage of 41.03%, particularly in developing self-confidence and managing emotions. The academic domain ranks second (32.70%), with a primary focus on time management techniques and effective learning strategies. Meanwhile, the social domain (11.77%) highlights students' needs in building healthy interpersonal relationships, while the career domain (14.03%) emphasizes the importance of guidance in planning a future aligned with students' potential and interests. The contribution of this study underscores the importance of strengthening guidance and counseling services in schools, focusing more on self-confidence development, emotional management, and effective learning strategies.Keywords: Needs Analysis Of Students, Educational Problems, Guidance, Personal Development.